Meningkatkan Penyesuaian Diri Siswa Terhadap Program Peminatan MIPA Melalui Bimbingan Klasikal Teknik Sosiodrama - Ayu Lailatuz Zakiyyah; Muslikah Muslikah (Universitas Kanjuruhan Malang, 2018)
The purpose of this research is to know empirically the effectiveness of classical sociodrama techniques to improve the adjustment of students ten class MIPA specialization program. The method of this research is experimental research, and use one group pretest-posttest design. Subjects were taken using simple random sampling technique with threety six students. The instrument that used in this research is the scale of adjustment to the MIPA specialization program. Data analysis using analysis describtive. The results showed that this study was effective. From the results of this research, It means that the classical guidance of sociodrama techniques is effective to improve the adjustment of students ten class MIPA specialization program.